Occurrence of Bursaphelenchus mucronatus (Nematoda: Aphelenchoididae) and the microhabitat distribution of fungi in declining pine trees in a locale in Korea. Issue 3 (13th May 2014) - Oh, In‐Jae; Ju, Wan‐Taek; Kim, Young‐Ju; Jung, Woo‐Jin; Kim, Kil‐Yong; Park, Ro‐Dong
Abstract A total of 33 pine trees with symptoms of decline were collected in Jeonnam Province, South Korea, and were examined for the presence of nematodes. About 20% of the trees sampled were positive with Bursaphelenchus species. All Bursaphelenchus species were found in recently dead or dying trees. Based on morphological observations, the nematode extracted from the declining pine trees was identified as B. mucronatus. The highly pathogenic pine wood nematode B. xylophilus was not found in any pine trees sampled. B. mucronatus was easily reared on fungus Botrytis cinerea. Twenty one fungal isolates were isolated from dead trees, fallen twigs, and healthy pine trees. The fungal isolates belonged to Trichoderma genus and were dominant in the wood of partially declining pines. The blue‐stain fungi transmitted by the Monochamus beetle were not detected. The B. mucronatus population decreased markedly on Auxarthron reticulatum DY‐2 isolated from soils. The number of nematodes also reduced on Verticillium saksenae A‐1, a nematophagous fungus, and Beauveria bassiana, an entomopathogenic fungus. This observation suggested the fungal production of nematicidal activity against B. mucronatus. When the fungal culture filtrates were also used for nematicidal activity on B. mucronatus, the culture filtrates of A‐1, DY‐2 and B. bassiana showed over 50% mortality within 48 h exposure. The fungi BC4, BC5 and BC6 isolated from declining pine trees inhibited the reproduction of B. mucronatus, and their culture filtrates also expressed nematicidal activity, indicating a possible interaction between the fungi in pine trees and nematodes at microhabitat level.